Human frontiers, environments, and disease : past patterns, uncertain futures - McMichael, A. J. (Anthony J.) (Cambridge University Press, 2001)
This compelling account charts the relentless trajectory of humankind across time and geography, and its changing survival patterns, from several million years ago when our ancient ancestors roamed the African Savannah to today's populous, industrialised, globalising world.